Fields2Benchmark: An open-source benchmark for coverage path planning methods in agriculture - Gonzalo Mier; Ana María Casado Faulí; João Valente; Sytze de Bruin (Smart Agricultural Technology)
The agricultural coverage path planning problem focuses on optimizing coverage paths for agricultural operations. Despite its importance, existing agricultural coverage path planning solutions are highly application-specific, limiting their generalizability and reproducibility. Fields2Cover offers a modular open source software library for coverage path planning, yet it lacks built-in means to benchmark its algorithms and to configure the workflow to specific tasks. It also fails on non-convex fields and operations that require reload trips. This paper introduces Fields2Benchmark, an open-source, modular benchmark designed to standardize the evaluation of agricultural coverage path planning algorithms. Fields2Benchmark includes a dataset with 350 real-world fields, featuring non-convex fields and in-field obstacles. The benchmark decomposes the problem into five units, i.e., field decomposition, headland generation, swath generation, route planning, and path planning— allowing researchers to evaluate and compare algorithms modularly. Each module supports interchangeable algorithms and objective functions, enabling customization for diverse use cases. Fields2Benchmark extends the existing Fields2Cover library by allowing task-specific choices, adding a module that splits a field into simpler parts, introducing new algorithms to shorten routes and handle refill needs, and adding tools to compare algorithms in isolation. Outputs are recorded as structured numerical data and visual representations to facilitate detailed analysis. The capabilities of the benchmark were validated on three use cases concerning field arrangement and route and path planning with and without capacity constraints. Results demonstrate its ability to handle complex field geometries, compare algorithms effectively, and evaluate computational performance. Fields2Benchmark is computationally efficient, with planning times suitable for real-time applications. It is supported by publicly available datasets and code. By standardizing agricultural coverage path planning evaluation, Fields2Benchmark aims to improve the reproducibility in this field, accelerating the research in agricultural robotics and field operations. For industrial robots, this benchmark cuts deployment costs, and shortens time to market, by simplifying the development process.